Economic and sociopolitical determinants of socio-environmental conflicts in Peru - León Mendoza, Juan Celestino (2019)
The purpose of this article was to identify the economic, social and political factors that contribute to the creation of social conflicts in Peru at a region level, including socio-environmental conflicts. For this purpose, using secondary data collected from the Ombudsman Office’s Social Conflicts Reports corresponding to the 2010-2017 period, econometric regressions were performed using the panel data methodology with fixed and random effects. According to the panel data model with fixed effects -selected with the Hausman Test-, social conflicts at regional level are directly determined by the gross domestic product per capita, the inequality in the distribution of income, the population’s good perception of the democratic electoral system, the number of people who sympathize with political positions that defend the environmental balance; and inversely related to the rate of underemployment in the labor market, the women’s income relative to men’s, the degree of participation of the mining and hydrocarbon sector in the regional production structure, and the percentage of people who use internet. Social conflicts are mainly environmental in nature and related to mining activity; however, the greater percentage share of mining production in the regional production structure implies a lower rate of conflicts if the other explanatory variables considered in the study stay the same. The research is correlated and applied.